2016
DOI: 10.1002/jbio.201600175
|View full text |Cite
|
Sign up to set email alerts
|

Low‐power laser irradiation in salivary glands reduces glycemia in streptozotocin‐induced diabetic female rats

Abstract: Low-power laser irradiation (LPLI) has been extensively employed to modulate inflammation in vitro and in vivo. Previous reports from our group indicated that LPLI might regulate glycemia in diabetic animals. Diabetes results in chronic hyperglycemia and therefore chronic inflammation by upregulation of inflammatory markers such as the high mobility group box 1 (HMGB1) protein. Thus this study aimed to analyze the LPLI effects upon blood glucose levels, plasma insulin and HMGB1 concentrations in a diabetes exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
4
6
0
2
Order By: Relevance
“…We also found a significantly decrease in animals blood glucose levels, this is consistent with our previous report, that shows that LPLI can improve the insulin sensitivity in diabetic rats, without changing the levels of HMGB1 or insulin in blood serum [26]. We observed the LPLI effect at 24 h, that provided large amounts of favorable data on inflammation and apoptosis in diabetic SMGs, however it must be considered that these findings may not translate to outcome of long-term studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found a significantly decrease in animals blood glucose levels, this is consistent with our previous report, that shows that LPLI can improve the insulin sensitivity in diabetic rats, without changing the levels of HMGB1 or insulin in blood serum [26]. We observed the LPLI effect at 24 h, that provided large amounts of favorable data on inflammation and apoptosis in diabetic SMGs, however it must be considered that these findings may not translate to outcome of long-term studies.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental diabetes-induced rat model was developed as described previously [26]. In brief, female Wistar rats (12-weeks old; n = 30) were purchased from University of Sao Paulo and were housed in isolation cages throughout the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, a single laser irradiation showed also an effect upon glycemic status, which was previously observed by our group and partially explained by Fukuoka et al study, where a decrease in insulin resistance (HOMA‐IR), an increase in insulin sensitivity (HOMA‐IS) and better β‐cells function (HOMA‐β) were observed in irradiated animals .…”
Section: Discussionsupporting
confidence: 89%
“…Previously, our studies showed an improvement in the salivary flow rate of normal rats after receiving laser irradiation . In addition, in diabetic animals, we observed a decrease of blood glucose concentration after PBMT, probably by improving the insulin resistance . We also investigated the action mechanism of this therapy upon SG and observed that laser irradiation decreased diabetes‐induced inflammation by reducing the induction of high‐mobility group box‐1 .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation